Airline seasonality: An explorative analysis of major low-cost carriers in Europe and the United States. (October 2022) - Zou, Li; Reynolds-Feighan, Aisling; Yu, Chunyan
Abstract: We develop two air traffic seasonality indices to complement the traditional Gini index. These measurements are adopted to assess the variability of air traffic over time and across the route network of low-cost carriers (LCCs) in Europe and the United States and to estimate the impact of seasonality on fleet utilization. Using panel data for nine LCCs in Europe and the United States from 2004 to 2017, we find that higher seasonality results in lower fleet utilization after controlling for stage length, network size, aircraft size, and fleet standardization. Moreover, we find that seasonality is negatively associated with spatial and climate zone diversification of airline route networks. These results suggest that airlines may be able to reduce seasonal traffic variability through diversifying their networks geographically and consequently mitigating the negative fleet utilization impact. Highlights: Alternative seasonality measures are developed for measuring the temporal-spatial characteristics of air traffic variability. The relationship between air traffic seasonality and climate diversification of airline route network is empirically studied. Seasonality is found to have a negative effect on fleet utilization based on panel data estimation. Köppen values are employed for measuring climate diversification of an airline's route network.